2020
DOI: 10.1111/jdi.13187
|View full text |Cite
|
Sign up to set email alerts
|

Achieving the composite end‐point of glycated hemoglobin <7.0% without weight gain or hypoglycemia with once‐weekly dulaglutide in Chinese patients with type 2 diabetes: A post‐hoc analysis

Abstract: Aims/Introduction: To assess the effect of dulaglutide (DU) 1.5/0.75 mg in comparison with glimepiride (GLIM) or insulin glargine (GLAR) on the composite end-point in Chinese type 2 diabetes patients. Materials and Methods: Post-hoc analyses of two randomized phase III trials (NCT01644500 and NCT01648582) were carried out using Fisher's exact test. The primary composite end-point was the number of patients reaching glycated hemoglobin (HbA1c) <7.0%, without weight gain and hypoglycemia. Secondary composite end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Moreover, in this post hoc analysis, compared to glimepiride, a significantly greater proportion of patients treated with dulaglutide (1.5 mg and 0.75 mg) reached a target HbA1c of \ 7.0%, with greater reductions in body weight and hypoglycemia at week 26. The finding of the present post hoc analysis is consistent with the post hoc analysis of AWARD-CHN1 and AWARD-CHN2 evaluating composite endpoints, in which 40-48% of patients on dulaglutide 1.5 mg, 30-39% of patients on dulaglutide 0.75 mg, and 15-20% of patients treated with active comparators (glimepiride/ insulin glargine) reached a target HbA1c of \ 7.0%, without weight gain or hypoglycemia at week 26 [19].…”
Section: Resultssupporting
confidence: 88%
“…Moreover, in this post hoc analysis, compared to glimepiride, a significantly greater proportion of patients treated with dulaglutide (1.5 mg and 0.75 mg) reached a target HbA1c of \ 7.0%, with greater reductions in body weight and hypoglycemia at week 26. The finding of the present post hoc analysis is consistent with the post hoc analysis of AWARD-CHN1 and AWARD-CHN2 evaluating composite endpoints, in which 40-48% of patients on dulaglutide 1.5 mg, 30-39% of patients on dulaglutide 0.75 mg, and 15-20% of patients treated with active comparators (glimepiride/ insulin glargine) reached a target HbA1c of \ 7.0%, without weight gain or hypoglycemia at week 26 [19].…”
Section: Resultssupporting
confidence: 88%
“…The results showed that exenatide (bid) was not inferior to PIA in terms of glycemic control, but was significantly better than PIA concerning the incidence of hypoglycemia and weight control.20 Another clinical study demonstrated that lixisenatide can effectively control blood glucose, and is highly effective in treating patients with elevated blood glucose due to relatively insufficient postprandial insulin secretion.Patients who received the treatment of lixisenatide could achieve weight loss within 24 weeks and had no risk of severe hypoglycemia.21The results of a clinical study on Chinese T2DM patients showed that the proportion of patients who did not gain weight or did not experience hypoglycemia after achieving the treatment goal of HbA1c<7.0% was significantly higher in patients using liraglutide compared with glimepiride (GLIM) and glargine insulin (GLAR). 22 In another study of East Asian patients (77% Chinese population), the incidence of hypoglycemia was significantly lower with dulaglutide 1.5 mg (5.7%) and dulaglutide 0.75 mg treatment (3.6%) than with the administration of glimepiride (15.6%).99 In addition to the lower risk of hypoglycemia, it was also shown that the administration of GLP-1RAs during hypoglycemia counteracted the endothelial dysfunction, oxidative stress, and inflammatory response the hypoglycemia triggered, which are likely to be related to the antioxidant activity of GLP-1RAs23 .…”
Section: Lower Risk Of Hypoglycemiamentioning
confidence: 99%